1977
DOI: 10.1111/j.0954-6820.1977.tb16861.x
|View full text |Cite
|
Sign up to set email alerts
|

Digitalis Therapy in a 70‐Year‐Old Population

Abstract: In the population study “70‐year‐old people in Gothenburg” 14% of the probands were found to be undergoing treatment with digitalis, 6% with digoxin, 6% with digitoxin and 2% with other glycosides. A comparison between results of the interview method and those of S‐digoxin analyses indicates that the interview method was acceptable. As far as can be judged from S‐digoxin analyses, only about 60% of the treated patients were on a dosage considered to be effective and free from obvious risks of side‐effects. Out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 20 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…In order to reduce the errors which follow with the interview technique, a registered nurse visited the subjects in their own homes and asked and helped the probands to put all drugs they used on a table whereafter the interview was performed. We have also made a control with S-digoxin analyses to test the reliability of the interview which was found to be very good for this drug (9). The high consumption does not reflect a corresponding high prevalence of diseases in the examined population.…”
Section: Discuss I 0 Nmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reduce the errors which follow with the interview technique, a registered nurse visited the subjects in their own homes and asked and helped the probands to put all drugs they used on a table whereafter the interview was performed. We have also made a control with S-digoxin analyses to test the reliability of the interview which was found to be very good for this drug (9). The high consumption does not reflect a corresponding high prevalence of diseases in the examined population.…”
Section: Discuss I 0 Nmentioning
confidence: 99%
“…We have tried to estimate the total prevalence of definable disorders and have found that 3040% of the probands at the age of 70 lacked diseases requiring drug treatment (10). Treatment for congestive heart failure and hypertension dominated and also for these diseases we have been able to show that there is a considerable overtreatment (9). Although the women were found to be healthier, they used more drugs than the men.…”
Section: Discuss I 0 Nmentioning
confidence: 99%
“…Digitalis is one of the most frequently prescribed drugs, especially among elderly people. Landahl et al (9) reported that 14% of the 70-year-old persons in Gothenburg were receiving digitalis. This treatment, that is sometimes initiated without any real indication (2,8,9), is seldom withdrawn.…”
mentioning
confidence: 99%